Developing a prioritization model for endoscopy and colorectal cancer 2-week wait referrals during the COVID-19 pandemic—is faecal immunochemical testing the answer?. Issue 1 (19th December 2020) - Habib Bedwani, N; English, W; Coda, S; Akinlade, F; Elzayat, I; Seward, E W; Hayee, B; Hanson, M; Banerjee, S
Abstract : The COVID-19 pandemic has significantly delayed 2-week wait (2WW) bowel cancer endoscopy. We propose a FIT (Faecal Immunochemical Test) based model to risk-stratify patients for 2WW endoscopy.